Zu den Konsulnfasten der Zeit des Antoninus Pius. Konsequenzen aus einem neuen Militärdiplom - Eck, Werner; Pangerl, Andreas (Studia Europaea Gnesnensia, 2017)
A new military diploma for the province Dalmatia mentions the pair of suffect consuls Q. Antonius I[sauricus, L. Aurelius Flaccus], known from the Fasti Feriarum Latinarum for May of an unknown year. Till now this pair was dated to the first years of Antoninus Pius, no later than 144 AD. But since in the diploma in the emperor’s title cos. IIII = 145 AD is mentioned, this is excluded. It seems that the suffect consuls can be dated only to one of the last years of Pius, either in 156 or 157, because in all the other years the consuls of the relevant months are known.